Ruptured Rudimentary Horn Ectopic Pregnancy: A Case Report - Rahman, Silvia; Barkat, Sabreena (Journal of Monno Medical College, 2025)
Rudimentary horn pregnancy, a rare form of ectopic pregnancy, occurs when the embryo implants in the rudimentary horn of an unicornuate uterus. This condition presents significant diagnostic and management challenges, often leading to life-threatening complications if untreated. This case study highlights the diagnosis, clinical management, and outcomes of a patient with a rudimentary horn pregnancy. Journal of Monno Medical College December, 2024;10 (2):104-106